Cryopreservation of Immature Oocytes at Germinal Vesicle Stage. When Gamete Maturation Performance Seems to Be Most Appropriate? - Yurchuk , Taisiia (Problems of Cryobiology and Cryomedicine, 2021)
Fertility preservation is among the priorities in reproductive medicine. However, the cancer patients and women with various functional ovarian disorders, wishing to preserve future reproductive potential may have some contraindications or no possibilities to cryopreserve mature oocytes and ovarian tissue. Therefore, the development of techniques for immature oocyte cryopreservation is considered an alternative strategy. Here, we have evaluated the survival, maturation, fertilization and embryo development rates of immature oocytes (Germinal vesicle (GV) stage – group 1) after cryopreservation and in vitro matured (IVM) ones (group 2) prior to cryopreservation, compared with in vivo matured metaphase-II (MII) oocytes (group 3). Survival rates were 97.6, 96.2 and 98.2 % for groups 1–3, respectively. The maturation rate of GV oocytes in group 1 was significantly lower than in group 2 and made 52.0 and 73.2%, respectively. The highest fertilization rate was revealed in group 3, and the lowest one was in group 1. The groups 1–3 showed the same tendency for further embryo development, i. e. the blastulation rates were 20.0, 38.5 and 56.9%, respectively. Thus, the survival rate of cryopreserved oocytes did not depend on their maturity rate. However, the IVM oocytes displayed lower fertilization and blastulation rates, than the in vivo matured ones. It was found that oocytes IVM should be performed prior to cryopreservation, because it ensured higher rates of maturation, fertilization and embryo development in vitro. Probl Cryobiol Cryomed 2021; 31(2): 161–167